Argentina - Crisis and Poverty 2003 : A Poverty Assessment, Volume 1. Main Report - World Bank (Washington, DC, 2013)
Argentina has gone through a major crisis in the past year, resulting in severe social dislocations, and a reduction of welfare by its poorest. The collapse of the Convertibility Plan, the freezing of bank deposits and the default on foreign debts, and the resulting high inflation, falling output and exchange rate devaluation, carried with it severe consequences for the poor. The break with the Convertibility Plan also meant that the adjustment in the labor market, occurred more through wages, rather than by an increase in unemployment. Inflation reduced real wages substantially, and, unlike previous recessions, unemployment arose largely from the formal sector, with an increase in employment in the informal sector. Many of the middle class, faced with both declining wages and freeze on bank assets, moved into poverty for the first time, carrying characteristics somewhat different than the traditional poor, including higher levels of education. Households appear to cope through a variety of strategies, including the entry into the workforce of those not previously employed, and reduced consumption of food, and other products. The Government's response to move to a floating exchange rate, and the consequent reduction in real wages, has provided the basis for a potential recovery. The reduction in real public sector wages, and pension obligations with inflation, while nominal revenues increased, has temporarily provided for an improved fiscal balance. The government, however, still faces serious issues in fiscal, and financial sector management. And Government programs still do not provide an adequate safety net for the unemployed on a permanent basis. Safety net programs are costly and duplicate other programs. Smaller, inefficient programs should be combined. Educational services need to be maintained, particularly with regard to payment of teachers, as the welfare effects go beyond the immediate income levels of teachers; in the health sector, gradual implementation of an infant and maternal health insurance, and the definition of, and agreement on provincial health goals (with monitorable health indicators) seem to be two key initial steps towards more effective protection for the uninsured poor, including other chronic inefficiencies in the health sector. Longer term poverty reduction measures include policy reforms towards higher levels of employment, access to basic services by the poor by improving infrastructure, and, improved human capital, and their productivity.